Isolation and Characterization Human Chorion Membrane Trophoblast and Mesenchymal Cells - Menon, Ramkumar (Placenta, 2020)
INTRODUCTION: To develop protocols for isolation and culture of human chorionic mesenchymal and trophoblast cells and test their differential responsiveness to oxidative stress METHODS: Chorion trophoblast cells (CTC) and chorion mesenchymal cells (CMC) were isolated from term fetal membranes by modifying current protocols. Their purity and characteristics were tested using bright field microscopy and after staining for cytokeratin (CK)-7 and vimentin. Cigarette smoke extract (CSE) was used to stimulate cells, and we determined reactive oxygen species (ROS) production using 2′7′-dichlorodihydro-fluorescein assay, stress signaler p38MAPK activation (Western blot) and senescence by flow cytometry. Co-treatment with antioxidant N-acetyl cystine (NAC) either alone or in combination with SB203580 (p38MAPK inhibitor) was used to test oxidative stress (OS)- and p38MAPK-mediated effects. RESULTS: The isolation and cell culture protocol used in this study yielded 92% pure CTC and 100% pure CMC. CSE treatment significantly induced ROS production, P-p38MAPK activation, and senescence in both cell types compared to controls. Cotreatment with NAC reduced ROS production and p38MAPK activation, and co-treatment with both NAC and SB203580 reduced senescence. ROS response in CMC was higher than CTC; however, senescence of CTC was 10-fold higher than CMC. CONCLUSIONS: We introduce approaches for proper isolation and culture of CTC and CMC without any influence or overgrowth of one specific type cell that can confound results. Using this approach, we determined differential effects of CTC and CMC to OS condition seen at term labor. Both CTC and CMC undergo p38MAPK-mediated senescence; however, the rate of senescence is higher in CTC.